Morphological observations on three Baltic species of Corynosoma Lühe, 1905 (Acanthocephala, Polymorphidae) - Leidenberger, Sonja; Boström, Sven; Wayland, Matthew T. (European Journal of Taxonomy, 2019)
Necropsies of Baltic grey (Halichoerus grypus) and ringed seals (Pusa hispida) presented a rare opportunity to study their acanthocephalan fauna. Both species hosted adults of three species of the genus Corynosoma Lühe, 1904, namely C. magdaleni Montreuil, 1958, C. semerme (Forsell, 1904) Lühe 1911 and C. strumosum (Rudolphi, 1802) Lühe 1904. A comparative morphological analysis of these three species of Corynosoma, combining both light and scanning electron microscopy, was performed for the first time. Sexual dimorphism in the size and shape of the trunk was observed in both C. magdaleni and C. semerme, but there was insufficient material to investigate this phenomenon in C. strumosum. Genital spines were not observed in any of the female acanthocephalans. Three possible explanations for the presence of genital spines in some females, but not others are (i) cryptic speciation, (ii) phenotypic variation and (iii) loss by extraction or shearing when the copulatory cap is released. Copulatory caps were observed on female C. semerme. The size and morphology showed considerable variability and all caps were strongly autofluoresecent.